An overview of nanofiber-based antibacterial drug design. (3rd April 2017) - Calamak, Semih; Shahbazi, Reza; Eroglu, Ipek; Gultekinoglu, Merve; Ulubayram, Kezban
ABSTRACT: Introduction: Conventional administration of antibacterial drugs to the human body can cause vital problems such as dose dependent systemic toxicity and bacterial resistance which prevent the healing process. In this regard, recent studies have been devoted to producing nanofiber based antibacterial drug delivery approaches which surpass bacterial resistance and toxicological issues. Areas covered: This review summarizes latest developments in the production of antibacterial nanofibers, nanofiber based antibacterial action mechanisms and release profiles of nanofibers. In the first section, key challenges of antibacterial nanofibers and release and non-release antibacterial action mechanisms of nanofibers are highlighted. In the second section, routes of antibacterial nanofiber design have been given. Factors affecting drug release mechanisms have been discussed elaborately in the final section. Literature was surveyed from research articles, standard sources (WOS and Scopus) and clinical trials. Expert opinion: New generation nanofibers provide high drug loading capacity and efficiency with their high surface area and tunable pore size. They also enable sustained and controlled release of antibacterial drugs with basic (direct incorporation, physically adsorption or chemically surface modification of antibacterial drugs), advanced (core–shell structure, nanoparticle decorated and multidrug loaded) and smart (stimuli responsive) antibacterial nanofiber design strategies.